PROSPECTIVE STUDY OF NEUROLOGICAL COMPLICATIONS OF DIPHTHERIA - ALI , S; ARSHAD , U; SADDIQUE , A; ZAHRA , N; KHAN , KAA; NAQVI , SZH (Biological and Clinical Sciences Research Journal, 2024)
Diphtheria remains a significant infectious disease, particularly in unimmunised and partially immunised populations. Neurological complications of diphtheria, though less commonly recognised, can have serious consequences if not promptly identified and treated. Objective: To examine the neurological complications associated with diphtheria, focusing on their onset, relationship with respiratory illness, and recovery patterns. Methods: This cross-sectional study was conducted at Nishtar Hospital Multan between January 2023 and January 2024. Thirty patients, aged 3 to 18 years, who were hospitalised with confirmed diphtheria and associated neurological complications, were included in the study. Demographic data, including age, gender, and vaccination status, were recorded, along with details of respiratory illness severity and symptoms of diphtheria-related complications. Comprehensive clinical and neurological evaluations were performed, supported by relevant investigations. Statistical analysis was conducted using [statistical software], with results presented as frequencies, percentages, and means where appropriate. Results: A total of 25 cases of diphtheria in which some sort of neurological complications developed were involved in this research. The mean age of the study population was 6.6 ±5.5 years, range 3-18 years. A latent interval of 4-49 days between the development of membranous tonsillitis and neurological problems was found. Isolated palatal paralysis was seen in 15 children (60%). All children(100%) showed nasal twang, regurgitation, and difficulty in swallowing as bulbar symptoms. Three children (12%) showed signs of third cranial nerve involvement, exhibiting ptosis and diplopia. Two children (8%) experienced unilateral lower motor neuron facial palsy. All 25 patients recovered completely. Recovery time they were ranged from 1-6 weeks for isolated bulbar palsy to 10-16 weeks for quadriparesis and 6 weeks for DP. Conclusion: Diphtheritic polyneuropathy should be recognised promptly by paediatricians and neurologists. Early identification and differentiation of various neuropathies are critical for effective treatment and contact tracing, with a generally favourable prognosis.